2020
DOI: 10.1152/ajpcell.00571.2019
|View full text |Cite
|
Sign up to set email alerts
|

Let-7d-5p suppresses inflammatory response in neonatal rats with necrotizing enterocolitis via LGALS3-mediated TLR4/NF-κB signaling pathway

Abstract: Necrotizing enterocolitis (NEC) is an acute intestinal condition accounting for severe mortality and morbidity in preterm infants. This study aimed to identify the possible roles of let-7d-5p in neonatal rats with NEC. The differentially expressed genes (DEGs) related to NEC were initially screened in silico. After establishment of NEC rat models, the measurement of the expression of let-7d-5p, galectin-3 (LGALS3), toll-like receptor 4 (TLR4) and nuclear factor kappa B (NF-κB) as well as proinflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…In the study conducted by Zhang et al 27 in an experimental Parkinson's animal model, it was reported that miR‐let‐7a suppresses microglia inflammation by targeting the STAT‐3 pathway. Sun et al 28 reported in their study on neonatal rats with necrotizing enterocolitis that miRNA‐let‐7d‐5p suppresses the inflammatory response via galectin‐3 (LGALS3)–mediated TLR4/NF‐B signaling. Marioto et al 29 investigated the expression profile of miRNAs associated with the immune response due to pulmonary infection at 28th and 56th days of infection in mice infected with Paracoccidioides brasiliensis.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Zhang et al 27 in an experimental Parkinson's animal model, it was reported that miR‐let‐7a suppresses microglia inflammation by targeting the STAT‐3 pathway. Sun et al 28 reported in their study on neonatal rats with necrotizing enterocolitis that miRNA‐let‐7d‐5p suppresses the inflammatory response via galectin‐3 (LGALS3)–mediated TLR4/NF‐B signaling. Marioto et al 29 investigated the expression profile of miRNAs associated with the immune response due to pulmonary infection at 28th and 56th days of infection in mice infected with Paracoccidioides brasiliensis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which Gal-3 regulates inflammatory response is multifaceted. In intestine, it stimulates pro-inflammatory responses by acting as ligands to TLRs of IECs [ 117 , 118 ] [Fig. 4 B].…”
Section: Immunomodulatory Nutrients For Intestinal Healthmentioning
confidence: 99%
“…4 B]. Previously, in rat pups, induction of experimental NEC was shown to activate Gal-3-mediated TLR4/NF-κB signaling [ 118 ]. Alternatively, Gal-3 act as PRRs to pathogens or LPS and recruit immune cells for opsonization [ 117 ] [Fig.…”
Section: Immunomodulatory Nutrients For Intestinal Healthmentioning
confidence: 99%
“…In recent years, the role of let-7d-5p in degenerative diseases such as Alzheimer’s disease and amyotrophic lateral sclerosis has been investigated, and it was significantly downregulated in both diseases ( Kumar et al, 2013 ; Mendes-Silva et al, 2016 ; Chen et al, 2018 ; Liguori et al, 2018 ). Moreover, let-7d-5p showed anti-inflammatory properties and inhibited intestinal epithelial cell apoptosis in necrotizing enterocolitis of neonatal rats by negatively regulating the LGALS3-dependent TLR4/NF-κB signaling pathway ( Sun et al, 2020 ). The expression of let-7d-5p was downregulated both in the skin of systemic sclerosis and in the lungs of PF ( Bagnato et al, 2017 ).…”
Section: Potential Mirna Targets For Pulmonary Fibrosismentioning
confidence: 99%